Activity-dependent calcium signaling and ERK-MAP kinases in neurons: a link to structural plasticity of the nucleus and gene transcription regulation - Wiegert, Simon; Bading, Hilmar (Cell calcium, 2011)
Activity-dependent gene expression is important for the formation and maturation of neuronal networks, neuronal survival and for plastic modifications within mature networks. At the level of individual neurons, expression of new protein is required for dendritic branching, synapse formation and elimination. Experience-driven synaptic activity induces membrane depolarization, which in turn evokes intracellular calcium transients that are decoded according to their source and strength by intracellular calcium sensing proteins. In order to activate the gene transcription machinery of the cell, calcium signals have to be conveyed from the site of their generation in the cytoplasm to the cell nucleus. This can occur via a variety of mechanisms and with different kinetics depending on the source and amplitude of calcium influx. One mechanism involves the propagation of calcium itself, leading to nuclear calcium transients that subsequently activate transcription. The mitogen-activated protein kinase (MAPK) cascade represents a second central signaling module that transduces information from the site of calcium signal generation at the plasma membrane to the nucleus. Nuclear signaling of the MAPK cascades catalyzes the phosphorylation of transcription factors but also regulates gene transcription more globally at the level of chromatin remodeling as well as through its recently identified role in the modulation of nuclear shape. Here we discuss the possible mechanisms by which the MAPKs ERK1 and ERK2, activated by synaptically evoked calcium influx, can signal to the nucleus and regulate gene transcription. Moreover, we describe how MAPK-dependent structural plasticity of the nuclear envelope enhances nuclear calcium signaling and suggest possible implications for the regulation of gene transcription in the context of nuclear geometry.